Telling the story of intersectional stigma in HIV‐associated Kaposi's sarcoma in western Kenya: a convergent mixed‐methods approach. (12th July 2022) - Collier, Sigrid; Singh, Rhea; Semeere, Aggrey; Byakwaga, Helen; Laker‐Oketta, Miriam; McMahon, Devon E.; Chemtai, Linda; Grant, Merridy; Butler, Lisa; Bogart, Laura; Bassett, Ingrid V.; Kiprono, Samson; et al.
Abstract: Introduction: The experience of stigma can be multifaceted for people with HIV and cancer. Kaposi's sarcoma (KS), one of the most common HIV‐associated cancers in sub‐Saharan Africa, often presents with visible skin lesions that may put people at risk for stigmatization. In this way, HIV‐associated KS is unique, as people with KS can experience stigma associated with HIV, cancer, and skin disease simultaneously. The aim of this study is to characterize the intersectionality of HIV‐related, cancer‐related and skin disease‐related stigma in people living with HIV and KS. Methods: We used a convergent mixed‐methods approach nested within a longitudinal study of people with HIV‐associated KS in western Kenya. Between February 2019 and December 2020, we collected quantitative surveys among all participants and conducted semi‐structured interviews among a purposive sample of participants. Quantitative surveys were adapted from the abridged Berger HIV Stigma Scale to assess overall stigma, HIV‐related stigma, cancer‐related stigma, and skin disease‐related stigma. Qualitative data were coded using stigma constructs from the Health Stigma and Discrimination Framework. Results: In 88 semi‐structured interviews, stigma was a major barrier to KS diagnosis and treatment among people with HIV‐associated KS. Participant's stories of stigma were dominated by HIV‐related stigma, more than cancer‐related or skin disease‐related stigma. However, quantitative stigma scores among the 117 participants were similar for HIV‐related (Median: 28.00; IQR: 28.0, 34.0), cancer‐related (Median: 28.0; IQR: 28.0, 34.8), and skin disease‐related stigma (Median: 28.0; IQR: 27.0, 34.0). In semi‐structured interviews, cancer‐related and skin disease‐related stigma were more subtle contributors; cancer‐related stigma was linked to fatalism and skin‐related stigma was linked to visible disease. Participants reported resolution of skin lesions contributed to lessening stigma over time; there was a significant decline in quantitative scores of overall stigma in time since KS diagnosis (adjusted β = –0.15, p <0.001). Conclusions: This study highlights the role mixed‐method approaches can play in better understanding stigma in people living with both HIV and cancer. While HIV‐related stigma may dominate perceptions of stigma among people with KS in Kenya, intersectional experiences of stigma may be subtle, and quantitative evaluation alone may be insufficient to understand intersectional stigma in certain contexts.